Voluntary daily fluctuation in dry matter intake is associated to feedlot performance, feeding behavior and rumen morphometrics in beef cattle - Pereira, I. C. [UNESP]; Costa, C. F. [UNESP]; Martins, C. L. [UNESP]; Pereira, M. C.S. [UNESP]; Squizatti, M. M. [UNESP]; Owens, F. N.; Cruz, G. D.; Millen, D. D. [UNESP]; Arrigoni, M. D.B. [UNESP] (Elsevier, 2021)
The degree of day-to-day fluctuation in voluntary DMI may influence feeding and rumination behavior, with potential impacts on feedlot performance. The purpose of this study was to evaluate the effect of voluntary fluctuation of DMI by pens of cattle given free-choice access to feed. These responses were measured in a dataset compiled from ten feedlot studies from 2006 to 2015. The data set included a total of 956 16-mo-old Bos indicus bulls (343.60 ± 44.15 kg) randomly allocated to a total of 238 pens (4 bulls per pen); cattle were fed high concentrate feedlot diets for an average of 106-d (minimum: 84-d; maximum: 140-d), and slaughtered at a commercial abattoir. To balance statistically for differences in animal background, type, and condition, for each year within treatments, pens were allocated into one of two groups: below or above the mean DMI fluctuation. The low- and the high- DMI fluctuation groups had day-to-day fluctuation in DMI of 5.18% and 6.22%, respectively (P < 0.01) or 0.45 vs. 0.55 kg/day (P < 0.01). Data were analyzed using a generalized linear mixed model procedure with the statistical software R. Cattle within the low-DMI fluctuation group had 4.2% greater (1.48 vs. 1.42 kg/d; P < 0.01) ADG and 3.7% greater (2.26 vs. 2.18 kg/d; P < 0.001) DMI expressed as a percentage of mean BW; but no significant effect was detected for G:F ratio (P = 0.91). Animals from the low-DMI fluctuation group had greater (P ≤ 0.01) daily increase in LM area and 12th rib fat as well as heavier HCW (266 vs. 263 kg; P = 0.04). Cattle from low-DMI fluctuation group consumed more DMI per meal (P < 0.001) and had greater NDF intake (P = 0.01) than cattle from the high-DMI fluctuation group. In addition, animals from high-DMI fluctuation pens took longer to consume and ruminate each kg of diet DM (P < 0.01) and NDF (P < 0.01) compared to cattle from low-DMI fluctuation group. A effect (P = 0.04) was detected for blood base excess (BEB) with low-DMI fluctuation pens having a greater concentration of BEB. Moreover, the low-DMI fluctuation group tended to have (P = 0.07) lower rumenitis scores. Although causal effects cannot be differentiated from casual relationships in this study, the fact that reduced daily DMI fluctuation was related to greater ADG and carcass weight makes this measurement relevant as an index of performance, and efforts to reduce DMI variability are warranted. Reducing day-to-day fluctuations in DMI should improve cattle health and performance.
Keywords: Feed intake; Fluctuation; Growth; Papillae; Performance